Modern urbanization has reshaped the bacterial microbiome profiles of house dust in domestic environments - Shan, Yifan; Guo, Jing; Fan, W.; Li, H.; Wu, H.; Song, Yong; Jalleh, Geoffrey; Wu, W.; Zhang, Brad (2020)
Background: The prevalence of allergy and other common chronic diseases is higher in developed than developing countries, and higher in urban than rural regions. Urbanization through its modification of environmental microbiomes may play a predominant role in the development of these conditions. However, no studies have been conducted to compare the microbiome in house dust among areas with different urbanization levels.